ANALISIS BIBLIOMETRIK: PENINGKATAN PEMBELAJARAN DENGAN PENDEKATAN ADAPTIF - Wawan Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to provide a comprehensive overview of Adaptive Learning. This study presents current research issues and future advances in Adaptive Learning from 2020 to 2023 through the Publish or Perish (PoP) database. The analysis consists of citation analysis and co-citation analysis. This bibliometric analysis review provides important insights for researchers to identify the most influential publications and determine their fundamental structure. Furthermore, this review facilitates future studies on influential research trends and emerging topics. The findings present several discussions based on klasters identified from the two analyses. Next, theoretical and methodological implications for the emergence of new subfields and exciting future work related to Adaptive Learning are presented. The results will assist academics and practitioners in advancing technology and helping Adaptive Learning ensure the continuity of student education during emergencies.